Professional and family responses to mental retardation in East Bengal and Bangladesh, 1770s-1990s - Miles, M (International journal of educational development, 1998)
Since the 1770s, formal knowledge about conditions later known as mental retardation (learning difficulities/disabilities) slowly accumulated with civil administrators, physicians, psychologists and teachers in East Bengal/Bangladesh. Factors in this growth of knowledge are reviewed. Most people with mental retardation and their families managed without professional advice. Some children with mental retardation were casually integrated in ordinary schools. Rooted in local cultures and concepts, the accumulated knowledge and experience of both families and professionals should be recognized, formulated and used in modern disability service planning. It risks being obscured by imported knowledge having greater prestige but less relevance